Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality Pada Materi Jaringan Komputer Dan Internet - Dwi Novita Hasan; Muhammad Rifai Katili; Sitti Suhada; Lanto Ningrayati Amali; Mukhlisulfatih Latief; Huzaima Mas'ud (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study was conducted based on students’ difficulties in understanding the concepts of computer networks and the internet, due to the use of learning media that were less effective at providing concrete visualization. Therefore, this study aims to develop Augmented Reality-based interactive learning media on the computer network and internet learning materials in Senior High School (SMA) as an alternative that provides a more interactive learning experience. This study employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted at SMA Negeri 1 Tolangohula in class X-5. The Augmented Reality-based learning media were developed using Unity, with validation by media and material experts and testing by students. The findings showed that the learning media were deemed valid, with media expert validation at 75% and material expert validation at 85%. The media were also categorized as practical, with a student practicality score of 87.76%. In addition, the AR learning media were deemed effective based on improvements in students’ learning outcomes, with an average pretest score of 52.5% and a posttest score of 83.75%, and an N-Gain score of 0.66, which was categorized as moderate. Thus, the developed AR learning media were considered feasible for use as learning media on computer networks and internet materials.